Homo infidelis: preferências, assimetria de informação e signaling - Nuccio, Adonay de (2013)
In this reseach we analyze the efficiency of signaling strategies in the context of extra-dyadic relationships. Aditionally, we measure both the declared preferences and revealed preferenced by individuals’ interactions in the virtual environment, comparing genders and countries. Previous researches about the extra-dyadic subject were based on methodologies with substancial gaps: low number of observations, samples restricted to college students, self-declared bias jeopardizing the precise interpretation of reality, and the absense of international comparisons. Suchs flaws were overcomed by this study. We analysed 100 thousand individuals, being 6 thousand men and 4 thousand women for each of the 10 countries of our sample: Argentina, Australia, Brazil, Canada, Chile, Italy, Mexico, Spain, UK and USA. Therefore, we have a vast sample in terms os nations and number of observations. Empirical evidences here revealed show that men are more active in the extramarital conquest, rebutting the suggestion of an eventual behavioral convergence between genders. Men contacted an average of 30 different women during the time window of 3 months, against 13 in the opposite direction. In terms of physical preferences, we verified that individuals from both genders look for an idealized partner to consummate the relationship. Women show interest in tall and experienced men. Men desire good shaped and younger women. Shorter and younger men, as well as older and taller women, were the most rejected individuals from the sample. In relation to the declared and revealed preferences about the type of desired extra-dyadic encounter, both men and women showed more interest in a fast affair, indicating the will in a shallow, casual and physical-sexual contact only, with low emotional bonds. The least chosen option was a 'virtual affair', suggesting the effective intention to materialize the infidelity, and not to keep it restrict to the virtual environment. Finally, we verified that the analyzed signaling stratetegies (through photos, feedback and virtual gifts) were strongly effective. In all cases individuals that adopted such tactics achieved a substantial competitive advantage in relation to those who didn’t, and due to that were endowed with greater attractiveness, receiving a high portion of messages and contacts.